The Role of Dyadic Coordination in Organizing Visual Attention in 5‐Month‐Old Infants. (20th July 2018) - Mason, Gina M.; Kirkpatrick, Fiona; Schwade, Jennifer A.; Goldstein, Michael H.
Abstract : In human infants, the ability to share attention with others is facilitated by increases in attentional selectivity and focus. Differences in early attention have been associated with socio‐cognitive outcomes including language, yet the social mechanisms of attention organization in early infancy have only recently been considered. Here, we examined how social coordination between 5‐month‐old infants and caregivers relate to differences in infant attention, including looking preferences, span, and reactivity to caregivers' social cues. Using a naturalistic play paradigm, we found that 5‐month‐olds who received a high ratio of sensitive (jointly focused) contingent responses showed strong preferences for objects with which their caregivers were manually engaged. In contrast, infants whose caregivers exhibited high ratios of redirection (attempts to shift focus) showed no preferences for caregivers' held objects. Such differences have implications for recent models of cognitive development, which rely on early looking preferences for adults' manually engaged objects as a pathway toward joint attention and word learning. Further, sensitivity and redirectiveness predicted infant attention even in reaction to caregiver responses that were non‐referential (neither sensitive nor redirective). In response to non‐referentials, infants of highly sensitive caregivers oriented less frequently than infants of highly redirective caregivers, who showed increased distractibility. Our results suggest that specific dyadic exchanges predict infant attention differences toward broader social cues, which may have consequences for social‐cognitive outcomes.